Inducing Critical Discourse Analysis in Speaking Syllabus for EFL Students of Indonesian Islamic Universities - Fauzan, Umar (Dinamika Ilmu, 2017)
Speaking courses are predominant to equip students oral proficiency and the stages of the improvement are required to include in the speaking syllabus.  This study was conducted to see the weaknesses of speaking course and renewal of speaking syllabus as the revision.  This study used content analysis and thematic analysis as the research design.  The study involved speaking lecturers,  students of speaking course, and head of English language education in IAIN Samarinda as research subjects.  Data on syllabus documents were obtained from the document analysis and data on the subjects’ perceptions were collected using interviews and questionnaire.  The study revealed that speaking courses were revised their names as: speaking for daily conversation, speaking for formal settings, speaking for academic settings, speaking for academic purposes, and public speaking.  Three primary characteristics of the renewal speaking sources were termed: learning outcomes, needs analysis based course contents, and CDA inductions.